2006
DOI: 10.1098/rsbl.2006.0494
|View full text |Cite
|
Sign up to set email alerts
|

The emerging amphibian pathogen Batrachochytrium dendrobatidis globally infects introduced populations of the North American bullfrog, Rana catesbeiana

Abstract: Batrachochytrium dendrobatidis is the chytridiomycete fungus which has been implicated in global amphibian declines and numerous species extinctions. Here, we show that introduced North American bullfrogs ( Rana catesbeiana ) consistently carry this emerging pathogenic fungus. We detected infections by this fungus on introduced bullfrogs from seven of eight countries using both PCR and microscopic techniques. Only native bullfrogs from eastern Canada and introduced bullfrogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
221
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(231 citation statements)
references
References 40 publications
8
221
1
1
Order By: Relevance
“…Furthermore, international trade and the presence of introduced hosts had positive effects on the distribution of Bd in both the MaxEnt and GLS models, and the HP analysis revealed that each of the FN and PP factors accounted for significant unique variation in the models. Previous studies had detected Bd on imported amphibian species in markets [42] and provided molecular evidence Table 2. A summary of model averaging and hierarchical partitioning (HP) analyses for the global distribution of Bd.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, international trade and the presence of introduced hosts had positive effects on the distribution of Bd in both the MaxEnt and GLS models, and the HP analysis revealed that each of the FN and PP factors accounted for significant unique variation in the models. Previous studies had detected Bd on imported amphibian species in markets [42] and provided molecular evidence Table 2. A summary of model averaging and hierarchical partitioning (HP) analyses for the global distribution of Bd.…”
Section: Discussionmentioning
confidence: 99%
“…The fungus colonizes the keratinized tissue of amphibian skin (Longcore et al 1999) and, in at least one species, causes death through osmotic and electrolyte imbalance (Voyles et al 2007). Species vary in susceptibility (e.g., Searle et al 2011), with responses ranging from mass mortality (Lips et al 2006), to tolerance of subclinical infection (Garner et al 2006), and to resistance (Marquez et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, North American bullfrogs (Rana catesbeiana) have frequently become feral in South America, Europe and Japan, where they consistently carry Bd, with the potential to transmit the pathogen to endangered native anurans [94]. Although there is limited evidence that it has been effective, non-selective culling of bullfrogs to control Bd has been proposed [95]. Culling of grey squirrels, which are a reservoir for a pox virus that threatens red squirrel populations, has also been suggested as a strategy to maintain red squirrel populations [96].…”
Section: (A) Isolating Infected Populationsmentioning
confidence: 99%